Upaya Peningkatan Pemahaman Pentingnya Imunisasi DPT pada Kader - Lusi Lestari; Heni Heryani; Fitri Nopianti; Fitri Nuraeni; Istikharoh; Intan Lestari (Yayasan Inspirasi El Burhani, 2022)
Introduction: Efforts to reduce the level of morbidity and mortality in children, one of which is the provision of immunization. DPT immunization is one of the mandatory immunizations given to children which aims to generate active immunity against diphtheria, pertussis, and tetanus at the same time. In addition to having benefits, DPT immunization also causes side effects in its implementation which can cause anxiety in mothers so that they do not want their children to get DPT immunization. An understanding of the importance of immunization is needed to reduce anxiety and increase the coverage of DPT immunization. Objective: The purpose of this health education is to increase understanding of the importance of DPT immunization for cadres Method: The method used is health education about the importance of DPT immunization through lectures and discussions with leaflet media. Result: The activity was carried out on Friday, September 23, 2022 at 13.00 WIB at the GOR Panykiran Village, Ciamis District. The total number of cadres who attended the health counseling activities was 30 people. The responses of the participants varied, but the majority were actively discussing. Conclusion: This health education has been successful, it can be seen from the enthusiasm and enthusiasm of the cadres who play an active role in participating in the activities and can answer the evaluation of the material that has been delivered.